Research and publications in Islamic perspective (Part 1) - M Zeki, Akram (KICT, 2021)
In this article, I will discuss some research and publications tasks from Islamic perspective, since this topic (research and publications) is part of our academic life, we always need to do different research activities, apply for research grants and supervise research works (including of supervising postgraduate research), the research works include many process such as searching for information, collecting of data, survey and review works, conducting a questionnaire and interview sessions, data analysis and statistical studies… etc.